2016
DOI: 10.1159/000452619
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Angiosarcoma: A Diagnostic Splenectomy Finding

Abstract: Splenic tumors are not frequent. Blood vessel neoplasms are a rare category of tumors and have an extremely low incidence in the spleen. This case report aims to describe a 57-year-old woman in whom a routine imaging examination had shown splenic cysts. During her follow-up, the cysts became larger and increased in number. A diagnostic splenectomy was performed and its analysis showed a rare splenic angiosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…More than 300 PSA cases have been described 4. Azevedo et al5 reported the case of a 57-year-old woman previously treated for breast ductal carcinoma, and as far as we know, to date, our case was the first case report of PSA with spontaneous rupture in a patient in Brazil.…”
Section: Introductionmentioning
confidence: 61%
“…More than 300 PSA cases have been described 4. Azevedo et al5 reported the case of a 57-year-old woman previously treated for breast ductal carcinoma, and as far as we know, to date, our case was the first case report of PSA with spontaneous rupture in a patient in Brazil.…”
Section: Introductionmentioning
confidence: 61%
“…Paclitaxel was considered as an adjuvant and neoadjuvant therapy by Vakkalanka and Milhem, [28] suggesting that chemotherapy may decrease local recurrence and improve overall survival. de Azevedo et al [29] also reported a patient remained disease free for 1 year and 2 months after paclitaxel adjuvant chemotherapy. Hara et al [30] presented a patient who received autologous peripheral blood stem cell transplantation combined with high-dose chemotherapy after splenectomy.…”
Section: Discussionmentioning
confidence: 99%